Motivation in Learning a Second Language: Exploring the Contributions of Family and Classroom Processes - Tam, Frank Wai-ming (Alberta Journal of Educational Research, 2009)
This study looks at how family and classroom factors influence second-language learning at the junior secondary level in schools in Hong Kong. It employed an ecological perspective to look at how family-level factors and classroom-level factors uniquely combine to influence students’ learning motivations in second-language learning. Nineteen secondary schools with over 2,200 secondary 1 and 2 students and their family members participated in the cross-sectional survey used for the research. Findings suggest that both teachers’ instructional behaviors and peer victimization norms in the classroom play a moderating role in the association between family processes and students’ motivation to learn English. It is suggested that the result of this research has important implications for home-school relations in Hong Kong as well as the restructuring of the school process to create a more supportive and nurturing environment for learning and teaching.